281PSelective depletion of tumour-associated SAMHD1 by HSP90 inhibitors enhances the anti-AML effect of cytarabine. (24th November 2019) - Sun, J; Zhang, Z; Huang, D; Hu, X; Yu, X
Abstract: Background: Acute myeloid leukemia (AML) is the most common acute type of leukemia in adults, with a disappointing prognosis and high death rate. Cytarabine (ara-C) is a primary first-line chemotherapy drug used in the treatment of AML, and resistance to it represents a major source of treatment failure. Sterile alpha motif and HD domain-containing protein 1 (SAMHD1), the only known human dNTPase, is known to attenuate ara-C cytotoxicity in AML cells, resulting in treatment failure and a poor prognosis. Therefore, selective inhibition of SAMHD1 in AML should prove a promising strategy for increasing the efficacy of ara-C. Nevertheless, no effective strategy to target SAMHD1 is available yet. Methods: Cell culture, Monocyte isolation and differentiation, Cytotoxicity assays, Protein extraction and Western blot analysis, Immunoprecipitation, Immunofluorescent staining, Tissue staining, Mass spectrum system, mRNA analysis, RNA silencing, Flow cytometry, Orthotopic AML animal model, Heterotopic AML animal model. Results: Here, we report that SAMHD1 is a novel HSP90-dependent protein in various tumor types. Pharmacological inhibition of HSP90 led to SAMHD1 depletion in a wide range of tumor cell types but had no or minimally effect on SAMHD1 of peripheral blood mononuclear cells (PBMCs) or macrophages from healthy donors due to the phosphorylation status on Thr 592. The combination of ara-C and HSP90 inhibitors showed a synergistic effect in killing AML cells. The HSP90 inhibitor also significantly enhanced the therapeutic efficacy of ara-C in both orthotopic and heterotopic models, alleviating tumor burden and prolonging survival. Conclusions: Overall, these data suggest that the addition of an HSP90 inhibitor to ara-C-based chemotherapy represents a potential new treatment strategy for AML patients. Legal entity responsible for the study: Xiaofang Yu. Funding: National Natural Science Foundation of China (81772169). Disclosure: All authors have declared no conflicts of interest.